PENINGKATAN PEMAHAMAN K3 PEKERJAAN KONSTRUKSI BAGI TUKANG BANGUNAN DI KECAMATAN MUARA GEMBONG, KABUPATEN BEKASI - Murtinugraha, R. Eka; Anisah (LPPM Universitas Negeri Jakarta, 2021)
Generally, construction workers in Indonesia have competency from experience, independent learning, and learning from their seniors. The construction workers started their careers starting from servants, repairmen, to becoming the head of a repairman, and some even could become foremen. They have never attended training or education specifically. Moreover, competency tests so that the aspects of OHS (Occupational Health and Safety) are often ignored. Construction workers generally do not understand in theory about the importance of equipping themselves with personal protective equipment in work, especially in OHS construction work which includes the work of formwork, cleaning, casting, and demolition. Through this training, construction workers are expected to be able to improve their experience by combining knowledge about OHS so that they can improve occupational health and safety, especially in Muara Gembong District, Bekasi Regency, West Java Province. The method of activity consists of the preparation and implementation stages. The preparation stage is observing the area and establishing communication with partners. Then, the implementation stage, namely debriefing about OHS construction work.